The rabies situation in Eastern Europe - Matouch, O (Developments in biologicals, 2008)
An overview of the rabies situation in the 19 countries of Central and Eastern Europe covering more than 2.5 million km2 is presented. In 2005, 6,500 cases of rabies were registered in this region with 31% in domestic animals and 69% in wild animals. Rabies was found in a limited number of dogs in 10 countries, and sporadically in three countries with seven cases in bats. A similar situation existed in 2006. Rabies is very rare in humans: 2 cases were reported in Belarus in 2006. Around 40,000 people are treated yearly due to rabies exposure. The main vector and reservoir is the red fox (Vulpes vulpes), with a 50% incidence in positive findings. The raccoon dog (Nyctereutes procyonoides) is another significant vector, mainly in the Baltics. Oral vaccination is used in varying degrees in 10 countries, with promising results. Two countries are currently rabies free, and several others are close to being rabies-free. An unfavourable situation remains mainly in the Baltics and nearby eastern countries, and also in some Balkan regions. All countries studied have national reference laboratories, appropriate legislation, and rabies as a notifiable disease.
Keywords: Animals; Dogs; Chiroptera; Animals, Domestic; Humans; lišky; vzteklina; východní Evropa; Europe, Eastern; Foxes; psík mývalovitý; divoká zvířata; lidé; psi; zvířata; Animals, Wild; vakcína proti vzteklině; Rabies Vaccines; Rabies; Disease Reservoirs; zdroje nemoci; hospodářská zvířata; Raccoon Dogs